Sulfur-nickel foam as cathode materials for lithium-sulfur batteries - Cheng, J.; Zhu, J.; Pan, Y.; Ma, Z.; Song, H.; Pan, J.; Li, Z.; Lu, Chunsheng (The Electrochemical Society, 2015)
Sulfur-nickel foam cathode materials prepared by an in situ solution-based method were served as electrode of lithium-sulfur (Li-S) batteries. At the rate of 0.5 C, the Li-S cells deliver an initial discharge capacity of 1340 mAh g–1 and 493 mAh g–1 after 500 cycles. It is shown that these Li-S cells are of high rate stabilities with a nearly 100% stable coulombic efficiency at various rates from 0.1 C to 5 C. The electrochemical stability of Li-S batteries is mainly due to the strong binding between the highly dispersed sulphur and nickel foam skeletons.